2018
DOI: 10.1103/physrevx.8.021054
|View full text |Cite
|
Sign up to set email alerts
|

High-Threshold Fault-Tolerant Quantum Computation with Analog Quantum Error Correction

Abstract: To implement fault-tolerant quantum computation with continuous variables, the Gottesman-Kitaev-Preskill (GKP) qubit has been recognized as an important technological element. However, it is still challenging to experimentally generate the GKP qubit with the required squeezing level, 14.8 dB, of the existing fault-tolerant quantum computation. To reduce this requirement, we propose a high-threshold fault-tolerant quantum computation with GKP qubits using topologically protected measurement-based quantum comput… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
229
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(243 citation statements)
references
References 63 publications
7
229
0
Order By: Relevance
“…Meanwhile, there have also been studies on scaling up the GKP code by concatenating it with a repetition code [22], the [ [4,2,2]] code [22,23], and the surface code [24][25][26], or by using cluster states and measurement-based quantum computation [25,27,28]. One of the recurring themes in these previous works is that the continuous error information gathered during the GKP code error correction protocol can boost the performance of the next layer of the concatenated error correction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, there have also been studies on scaling up the GKP code by concatenating it with a repetition code [22], the [ [4,2,2]] code [22,23], and the surface code [24][25][26], or by using cluster states and measurement-based quantum computation [25,27,28]. One of the recurring themes in these previous works is that the continuous error information gathered during the GKP code error correction protocol can boost the performance of the next layer of the concatenated error correction.…”
Section: Introductionmentioning
confidence: 99%
“…One of the recurring themes in these previous works is that the continuous error information gathered during the GKP code error correction protocol can boost the performance of the next layer of the concatenated error correction. For example, while the surface code by itself has the code capacity threshold ∼11% [15], the threshold can be increased to ∼14% if the additional error information from GKP-stabilizer measurements is incorporated in the surface code error correction protocol [24][25][26]. These code capacity thresholds are, however, computed by assuming noiseless GKP and surface code stabilizer measurements, or equivalently, by assuming that ideal GKP states (with an infinitely large squeezing) are used for the stabilizer measurements.…”
Section: Introductionmentioning
confidence: 99%
“…This work opens the possibility of all-optical implementation of various nonlinear interactions which are currently available only at mechanical or microwave frequencies, and motivates advanced integrated optical setups. Conditional quantum Rabi gates by current hybrid quantum optics technology are directly applicable to extend quantum repeaters for secure quantum optical communication [100][101][102][103] and in future, combine it with error correction strategies [104][105][106][107][108][109]. It will stimulate further the development of other implementations of the RI and other deterministic nonlinear interactions beyond rotating-wave approximation at the optical frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…By performing the error correction scheme of [9], measuring the q and p quadratures to perform error correction will always project the state onto a state with a single shift error in q and p. Lastly, we point out that d in definition 5 relates to the largest allowed size of the shift error which occurs during the protocol. This should 5 Using the optimizations considered in [18], using Knill error correction could potentially increase the threshold of p 6 to a larger value.…”
Section: Fault-tolerant Definitionsmentioning
confidence: 99%
“…photon loss), recently it has been shown that GKP codes have better error correction capabilities than such codes under the assumption of perfect encoding and decoding [1][2][3]. In addition, it has been shown how GKP codes can be concatenated with the toric code in order to achieve larger threshold values compared to toric codes with bare physical qubits [4][5][6]. Lastly, given a supply of GKP-encoded Pauli eigenstates, universal fault-tolerant quantum computation can be achieved using only Gaussian operations [7].…”
Section: Introductionmentioning
confidence: 99%